Peran Jabatan Notaris Untuk Pelindungan Data Pribadi Pada Akta Autentik Berdasarkan Undang-Undang Nomor 27 Tahun 2022 Tentang Pelindungan Data - Gunawan, Maria Hartanty; Lukman, FX Arsin (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
A Notary is every person who assumes and performs duties as a public official authorized to make authentic deeds and other authorities as regulated in laws and regulations. In carrying out his authority, a notary is required to obey the rules, policies and prohibitions that are regulated explicitly in Law no. 30 of 2004 jo. UU no. 2 of 2014 (UUJN). With the enactment of Law no. 27 of 2022 concerning Protection of Personal Data (UUPDP), a review must be applied to the obligations of a notary, especially their obligations to protect and keep confidential personal data listed in the notary deed. Through doctrinal research methods or literature studies and statutory approaches, the authors found that there is some data in the notarial deed that falls into the scope of personal data. In addition, the authors also found that the sanctions regulated by the UUJN and UUPDP have similarities and also differences, so further arrangements are needed in this regard. Unlike the UUJN, criminal sanctions are regulated in detail in the UUPDP so that actions that harm the owner of personal data can be subject to criminal penalties in the form of imprisonment or fines. Thus, notaries must also pay attention to the obligations and prohibitions regulated in the UUPDP because a notary is also a Personal Data Controller based on this research.